Factors influencing general music teachers’ attitudes and practices regarding multicultural music education / Wong Kwan Yie - Wong, Kwan Yie (2014)

(untitled)
This study has two fold purposes to examine 1) the level of multiculturalism in terms of life experience, personal attitudes, personal behaviour, and professional behaviour amongst the general music teachers; and 2) the utilization of multicultural music education by the teachers in curriculum and activities. More specifically, this study also intends to explore the relationship between the general music teacher’s behaviour and their efforts in developing and implementing multicultural music education in music classes. The simple random sampling procedure was used in this study. The subjects included the primary schools’ general music teachers (N=456) in the Klang Valley, Malaysia. To address the purpose of the study, the quantitative survey questionnaires were used. The two existing modified survey instruments, namely the Personal Multicultural Assessment and the Music Specialist’s Multicultural Music Education Survey, were used in this study upon the permission-to-use granted by the respective researchers. The Personal Multicultural Assessment was used to measure the level of general music teachers’ multiculturalism while the Music Specialist’s Multicultural Music Education was used to measure teachers’ attitudes and practices regarding multicultural music education. Data analysis included descriptive statistics, analysis of variance (ANOVA), correlational analysis (Pearson product-moment correlation), and multiple regression to assess and evaluate the relationship between teacher’s life experience, personal attitudes, personal behaviour, and professional behaviour; and their developing and employing of multicultural music education. iv In general, this study found that the primary schools’ general music teachers (N=456) in the Klang Valley, Malaysia are functioning at varying levels of multiculturalism. The teachers’ Personal Multicultural Assessment mean scores ranked at the second level of the Multicultural Personae Construct in the areas of life experience, personal attitudes, personal behaviour and on the composite score. The area of personal attitude was ranked the lowest mean scores among the four subscales. On the other hand, score was highest on the professional behaviour subscale which ranked at the third level of the Multicultural Personae Construct. Results of One-Way of Analysis of Variance (ANOVA) procedures indicated that ethnic identity and religion had significant effects on the life experience subscale, personal attitudes subscale, personal behaviour subscale and the composite scale of Personal Multicultural Assessment. However, the only variable that had a significant effect on the professional behaviour subscale scores of the general music teachers was religion. General music teachers from the Klang Valley ranked the category of “Definition of multicultural music education” as the highest and “Training and support with multicultural music education” as the lowest among the four classifications of Music Specialist’s Multicultural Music Education Survey. Gender and religion had significant effects on the Music Specialist’s Multicultural Music Education Survey. The results of this study also indicated that life experience, personal attitudes and professional behaviour among primary schools’ general music teachers’ multiculturalism were the significant contributors to their utilization of multicultural music education.